Asal-usul dan Transformasi: Pencak Dor dari Latihan Santri hingga Hiburan Rakyat - Rifiy Qomarrullah; Fredrik Sokoy (Lembaga Pengembangan Kinerja Dosen, 2025)
Pencak Dor is a traditional martial art rooted in Islamic boarding schools (pesantren) in Java, originally serving as physical training and discipline-building for students (santri). Over time, Pencak Dor has undergone a transformation from an internal pesantren activity into a popular form of public entertainment. This study aims to explore the origins of Pencak Dor and analyze its transformation from a socio-cultural perspective. The research employs a literature review method combined with content analysis of secondary sources, including books, scholarly articles, historical archives, and online media. The findings reveal that the transformation of Pencak Dor is driven by internal factors such as the adaptation of pesantren cultural values, as well as external influences like the development of mass media and the commercialization of performing arts. Despite changes in form and function, values such as sportsmanship, togetherness, and local wisdom have been preserved. This study highlights the importance of preserving Pencak Dor as a cultural heritage that remains adaptive to the dynamics of time.